A standalone Internet cognitive behavior therapy treatment for social anxiety in adults who stutter: CBTpsych - Helgadottir, F; Menzies, R; Onslow, M; Packman, A; O'Brian, S (Elsevier, 2014)
Highlights • There are few clinical psychology CBT experts who are specialised in stuttering. • Scalable fully automated computerized cognitive behaviour therapy has been developed called the CBTpsych. • Preliminary data suggest CBTpsych engages clients to participate in the tasks instructed by the program. • Five of seven participants with social anxiety disorder diagnosis lost their diagnosis with CBTpsych after a 5-month period. • Symptoms of social anxiety reduced and participant quality of life improved. Purpose Social anxiety is common for those who stutter and efficacious Cognitive Behavior Therapy (CBT) for them appears viable. However, there are difficulties with provision of CBT services for anxiety among those who stutter. Standalone Internet CBT treatment is a potential solution to those problems. CBTpsych is a fully automated, online social anxiety intervention for those who stutter. This report is a Phase I trial of CBTpsych. Method Fourteen participants were allowed 5 months to complete seven sections of CBTpsych. Pre-treatment and post-treatment assessments tested for social anxiety, common unhelpful thoughts related to stuttering, quality of life and stuttering frequency. Results Significant post-treatment improvements in social anxiety, unhelpful thoughts, and quality of life were reported. Five of seven participants diagnosed with social anxiety lost those diagnoses at post-treatment. The two participants who did not lose social anxiety diagnoses did not complete all the CBTpsych modules. CBTpsych did not improve stuttering frequency. Eleven of the fourteen participants who began treatment completed Section 4 or more of the CBTpsych intervention. Conclusions CBTpsych provides a potential means to provide CBT treatment for social anxiety associated with stuttering, to any client without cost, regardless of location. Further clinical trialing is warranted.